2007
DOI: 10.1086/522911
|View full text |Cite
|
Sign up to set email alerts
|

Successive Flaring during the 2005 September 13 Eruption

Abstract: We report a detailed analysis of successive flaring during the X1.5 event in the NOAA AR 0808 on 2005 September 13. We identify a filament lying at the southeast boundary of the active region as the physical linkage between the two flares in close succession. It is noticeable that the filament erupted $13 minutes after the initial flare onset at $19:22 UT near the central magnetic polarity inversion line (PIL). During this time period, the filament only showed a slow rising; meanwhile, a spatially associated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
(38 reference statements)
9
16
0
Order By: Relevance
“…3, left panel), approximately 3 h prior to its eruption at ∼19:24 UT. Other studies of this filament eruption have been carried out independently by Nagashima et al (2007) and Wang et al (2007). We observed the activation of the filament mainly in TRACE images taken in the 195 Å passband (Fig.…”
Section: September 13 (Event 1: On-disk)supporting
confidence: 67%
See 1 more Smart Citation
“…3, left panel), approximately 3 h prior to its eruption at ∼19:24 UT. Other studies of this filament eruption have been carried out independently by Nagashima et al (2007) and Wang et al (2007). We observed the activation of the filament mainly in TRACE images taken in the 195 Å passband (Fig.…”
Section: September 13 (Event 1: On-disk)supporting
confidence: 67%
“…Events 4 and 5 of Table 1 are two examples of such eruptions. Earlier observations reported by Wang & Shi (1993) showed a filament eruption characterised by an untwisting upward motion associated with a localised precursor "microflare" representing the first signature for the disturbance of the system. In conformity with the conclusions drawn from event 4 discussed in this paper, Wang & Shi (1993) found that canceling magnetic reconnection beneath the filament can be responsible for the untwisting and upward motion.…”
Section: Discussionmentioning
confidence: 92%
“…Namely, the transverse field near the magnetic polarity inversion line (PIL) at the core flaring region is enhanced rapidly and irreversibly, which is often accompanied by an increase of magnetic shear. Such a rapid change of vector PMFs closely associated with flares/CMEs has been consistently found later on using ground-based (Schmieder et al 1994;Wang et al 2002Wang et al , 2004bWang et al , 2005Wang et al , 2007Liu et al 2005;Su et al 2011) and Hinode observations (Jing et al 2008;Li et al 2009). Indirect evidence includes the unbalanced flux evolution of the line-of-sight magnetic field , the variation of the sunspot white-light structure in flaring regions (Wang et al 2004a;Deng et al 2005;Liu et al 2005;Chen et al 2007), and the change in the pattern of the penumbral Evershed flow (Deng et al 2011).…”
Section: Introductionsupporting
confidence: 58%
“…It occurred from 23:15 to 23:30 UT on 2005 September 13 in AR 10808. Several papers analyzed this event and associated phenomena, for example, the related radio bursts (Oberoi et al 2009), or CME (Wang et al 2007;Liu et al 2009), or filament (Nagashima et al 2007), or magnetic configuration (Li et al 2007). Figure 1 shows the SOHO/MDI magnetogram at 23:23:03 UT with RHESSI (PIXON) contours at 23:18:00 UT (a) and 23:19:30 UT (b) respectively.…”
Section: Observation and Measurementmentioning
confidence: 99%